Correlating macroscopic plant growth parameters to nanomechanical properties of cellulose microfibrils - Nabila Masud; Jie Tang; Hasibul Hasan Hasib; Talukder (Zaki) Jubery; Xuan Xuan Lee; Hongqing Guo; Anwesha Sarkar (Current Plant Biology, 2024)
The plant cell wall, a vital component in providing structural integrity and facilitating growth, comprises cellulose microfibrils among its major constituents. This study employed Atomic Force Microscopy (AFM) to investigate the intricate relationship between genetic mutation, cellulose microfibril organization, nanomechanical properties of cellulose microfibrils and plant growth. Focusing on the Arabidopsis thaliana wild type (WT) and ixr1–2 mutant population (known for resistance to herbicide ISOXABEN), we utilized AFM to scrutinize cellulose microfibrils on the newly synthesized cell wall in 5-day-old dark-grown hypocotyls. Our macroscopic analysis revealed significant differences in plant growth, prompting a detailed examination at the nanoscale using AFM to discover if the macroscopic disparity between these two populations gets translated in structural details, orientation, and mechanical properties of cellulose microfibrils at the nanoscale too. AFM analysis highlighted distinct organizational disparities in cellulose microfibrils between the WT and mutant population. Our results revealed that the WT manifests a more aligned and oriented microfibril structure in contrast to the mutant population that shows significantly less aligned cellulose microfibrils in the plant growth direction. Also, the WT and mutant population demonstrate nuanced differences in height, width, roughness, deformation, and stiffness. The observed nanoscale alterations in microfibril structure and nano-mechanical properties contribute to an improved understanding of the intricate dynamics governing plant cell wall structure and its pivotal role in growth and development.